A STUDY ON THE EFFECT OF DIABETES MELLITUS ON THE CLINICAL OUTCOME AMONG PATIENTS WITH COVID-19 - SANNAN , M; GUL , MM; NASIM , Z; KHAN , SU; ULLAH , A; NASIR , R (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to investigate how diabetes mellitus affects the clinical outcomes of patients with COVID-19. The study was conducted between November 2022 and April 2023 at the Department of Medicine in Khyber Teaching Hospital, Peshawar. We included 40 diabetic COVID-19 patients and 40 non-diabetic COVID-19 patients in our research and examined the incidence of sepsis, acute respiratory distress syndrome (ARDS), and mortality. The results showed that diabetic COVID-19 patients had significantly higher mortality, sepsis, and ARDS rates than non-diabetic COVID-19 patients. Mortality was reported in 22.5% of diabetic patients compared to 5% of non-diabetic patients (P = 0.01). The incidence of sepsis was 25% among diabetic patients and 5% among non-diabetic patients (P = 0.02). Similarly, ARDS was reported in 35% of diabetic patients compared to 10% of non-diabetic patients (P = 0.007). In conclusion, our study suggests that diabetes significantly worsens clinical outcomes among patients with COVID-19.